Surgical Management of Cleft Lip and Palate A Comprehensive Atlas - Nadjmi, Nasser (Springer International Publishing, 2018)
This atlas provides comprehensive, step-by-step guidance on surgical management of the cleft lip, alveolus, and palate. In particular, it demonstrates how an anatomical approach to management provides a sound basis for dealing with the many variations in cleft type. The displaced anatomical borders and landmarks, as well as the functional and aesthetic units, are fully described. The art of dissecting them from their abnormal position is illustrated, and their reconstruction into a normal and functional shape is meticulously explained. The main treatment philosophy underlying the described approach is that children born with cleft deformity should be "cleftless" by the time they enter the first grade of primary school. They must have normal speech. They should not have a fistula or residual cleft in the palate and/or the alveolus. And they should have a normal face so that they can confront the challenges of life without cleft stigmata. Both novice and more experienced surgeons will find this atlas to be a valuable aid to optimal treatment, and readers will have online access to videos of the described surgical procedures.